1999
DOI: 10.1023/a:1008372529239
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of first-line LY231514 (multi-targeted antifolate) in patients with locally advanced or metastatic colorectal cancer: An NCIC Clinical Trials Group study

Abstract: Single-agent MTA at 500 mg/m2 given every three weeks has modest activity in metastatic colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 7 publications
0
58
1
Order By: Relevance
“…Pemetrexed 500 or 600 mg/m 2 was administered as a 10-minute infusion once every 21 days. The lower dose of 500 mg/m 2 was instituted due to toxicities seen both in the study by Rusthoven et al [3] and a colorectal study by Cripps et al [6] conducted at the same institution. Results from the study by Rusthoven et al [3] and one by Clarke et al [2] were consistent with regard to end points, with an overall response rate of 23% [3] and 18% [2] (Table 3).…”
Section: Nsclcmentioning
confidence: 99%
“…Pemetrexed 500 or 600 mg/m 2 was administered as a 10-minute infusion once every 21 days. The lower dose of 500 mg/m 2 was instituted due to toxicities seen both in the study by Rusthoven et al [3] and a colorectal study by Cripps et al [6] conducted at the same institution. Results from the study by Rusthoven et al [3] and one by Clarke et al [2] were consistent with regard to end points, with an overall response rate of 23% [3] and 18% [2] (Table 3).…”
Section: Nsclcmentioning
confidence: 99%
“…The maximum tolerated dose established in Phase I studies of pemetrexed was 600 mg/m 2 every 3 weeks (4,5). This dose was later reduced to 500 mg/m 2 every 3 weeks in several Phase II trials, particularly when used in combination with other cytotoxic agents (6,7). Folic acid and vitamin B 12 supplementation became a requirement for pemetrexed-based therapy early in this study, when analysis of safety data from multiple pemetrexed trials suggested that supplementation may decrease toxicity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Pemetrexed has shown broad clinical antitumor activity in patients with colorectal, pancreatic, and breast cancers (Adjei et al, 2004) and has received regulatory approvals for treating patients with malignant mesothelioma and nonsmall cell lung cancer (Hazarika et al, 2004). Pemetrexed 500-600mg/m² administered every three weeks showed singleagent activity as first-line treatment for advanced CRC in two phase II trials (Cripps et al, 1999;John et al, 2000). The objective responses rates were 15% in the American study (John et al, 2000) and 17% in the Canadian study (Cripps et al, 1999) and the median overall survival times were 16.2 and 15.1 months, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pemetrexed 500-600mg/m² administered every three weeks showed singleagent activity as first-line treatment for advanced CRC in two phase II trials (Cripps et al, 1999;John et al, 2000). The objective responses rates were 15% in the American study (John et al, 2000) and 17% in the Canadian study (Cripps et al, 1999) and the median overall survival times were 16.2 and 15.1 months, respectively. The major toxicities of pemetrexed are myelosuppression, skin rash, and mucositis, with neutropenia being the primary doselimiting toxicity (Louvet et al, 2004).…”
Section: Resultsmentioning
confidence: 99%